Evaluating literacy levels of patient education materials for a sickle cell transition group education programme. (April 2020) - Johnson, Robin; Edwards, Ronisha; Rivers, Angela; Patil, Crystal; Walsh, Susan
Objective: A multidisciplinary team from a US midwestern urban medical centre developed written patient education materials for a group education programme designed to prepare adolescents and emerging adults with sickle cell disease for transition to adult care. We evaluated the literacy levels of these materials and demonstrate how to revise the patient education materials to meet literacy standards. Method: Six tools were used to evaluate literacy levels of the patient education materials. Based on the literacy level scores of the materials, including readability, grade level, understandability and actionability, recommendations and revisions were made to improve literacy levels. The revised materials were again assessed using the same six tools. Results: Initial literacy levels of the patient education materials were higher than recommended standards. Adjustments were made to meet literacy standards. Not all standards were met. Conclusion: Patient education materials should conform as much as possible to recommended literacy standards for optimum understandability. However, not all patient education materials can fully meet all evidence-based literacy standards. Recommendations for evaluating literacy standards when creating or providing previously developed patient education materials are discussed. Extra efforts to achieve acceptable literacy standards are recommended when medically complex educational materials are necessary.